Deep Learning-Based Islamic Education Transformation : Innovation in Islamic Learning in the Digital Era - Arini Rochyati (International Journal of Islamic Educational Research, 2025)
The development of information technology and digitalization has transformed almost all aspects of human life, including the world of education. The era of the Industrial Revolution 4.0 to Society 5.0 has given rise to new demands on the education system, including in the field of Islamic Religious Education (PAI). In PAI learning can no longer be maintained with a traditional approach that only focuses on lectures and memorization. Along with technological developments and changing demands of the times, especially the era of Society 5.0, PAI learning faces new challenges that require innovation and adaptation in learning approaches. Within this framework, the deep learning approach or in-depth learning is one strategy that can improve the quality of learning (Suwandi et al., 2024) including in the field of Islamic Religious Education (PAI). This study aims to describe the basic concepts and principles of deep learning in PAI learning, describe the transformation of PAI learning based on deep learning, describe the benefits, opportunities, and challenges faced in implementing deep learning in PAI learning and describe a PAI learning model based on deep learning that can improve students' 21st-century competencies without eliminating Islamic spiritual values. This study employed a library research method to analyze and understand the transformation of deep learning-based Islamic education in the digital era, based on relevant literature sources. The study results indicate that the Deep Learning Approach to Islamic Religious Education (PAI) offers significant potential as a learning innovation relevant to the digital age. With a model that incorporates mindful, meaningful, and joyful learning, Islamic Religious Education (PAI) can be a lesson that is not boring but transformative, developing students' intellectual and spiritual well-being. Successful implementation depends heavily on teacher preparedness, a flexible and relevant curriculum, technological support, and a school culture that encourages active participation and reflection.